Adaptive Governance in Carbon Farming Policies - Torabi, Nooshin (Springer International Publishing : Imprint: Palgrave Pivot, 2019)
This book discusses a variety of different perspectives involved in biodiversity management and bio-sequestration projects in Australia, working towards achieving adaptive governance in carbon farming. It not only examines landholders' motivation but also the challenges of integrating biodiverse forests into the agricultural landscape. Drawing on the contrast between science and policy stakeholders' views on carbon farming and the practical challenges of achieving adaptive governance, the book discusses the significant gap between theory and practice encountered in this field of study. The book suggests ways of improving the decision-making capacity of government officials and policymakers involved in managing carbon and biodiversity markets, as well as introducing measures to promote adaptive governance by engaging landholders in more effective land conservation. Climate change is a pressing issue on the global political agenda, and this book makes an important contribution to the ongoing debate. This book will be an invaluable reference for practitioners, policymakers and researchers interested in alternative forms of governance in natural resource management.